Analisis Manajemen Penimbunan Batubara pada Area Stockpile di PT. Barito Bangun Nusantara - Manissa Rahayu; Deddy Nan Setya Putra Tanggara; I Putu Putrawiyanta; Lisa Virgiyanti; Yustinus Hendra Wiryanto (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
PT. Barito Bangun Nusantara is a company engaged in coal exploration and production activities, where the production is temporarily stored in a stockpile area before being processed or distributed. Stockpile management requires attention to several important factors, such as area design and stockpiling methods, so that storage runs effectively and does not cause a decrease in coal quality. This study was conducted on old and new stockpiles with the aim of analyzing the actual stockpiling conditions and providing technical recommendations regarding the ideal stockpile capacity and configuration. The research methods included field observation, primary and secondary data collection, and descriptive quantitative analysis. The results showed that both stockpiles experienced inefficiencies due to excess capacity. The actual tonnage reached 49,191.98 tons, exceeding the planned capacity of 35,000 tons, with a stockpile height reaching 9 m. This condition caused long stacking times and the FIFO system did not operate optimally. The study recommended an ideal stockpile capacity of 30,740.61 tons, with a maximum height of 8 m. The recommended angle of repose for the old stockpile is 30°, with a capacity of 11,542.19 tons, while for the new stockpile, it's 34°, with a capacity of 19,198.42 tons. This arrangement is expected to allow for a smoother unloading process and a more ideal stockpile.